THE ROLE OF CRIMINAL SANCTIONS AND CIVIL LIABILITY IN THE RESOLUTION OF DISPUTES CONCERNING CONFIDENTIAL INFORMATION AND INTELLECTUAL PROPERTY - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2026)
This article discusses the contribution of criminal sanctions and civil liabilities in the resolution of disputes concerning confidential information and intellectual property. The focus of the study is on how these two legal instruments operate differently yet complement one another in protecting the interests of rights holders. The research method employed is a literature review using a normative legal approach, involving an examination of legislation, academic journals and relevant legal literature. The findings indicate that criminal sanctions serve as a deterrent and a means of curbing infringing behaviour, particularly in relation to the disclosure of trade secrets and unauthorised copyright infringement. Meanwhile, civil liabilities play a role in redressing losses through compensation, the cessation of infringements, and more flexible dispute resolution mechanisms. Both underscore that legal protection for confidential information and intellectual property is not only aimed at punishing offenders but also at restoring the rights of the aggrieved party in a fair and proportionate manner.